2019
DOI: 10.1089/cyber.2019.0146
|View full text |Cite
|
Sign up to set email alerts
|

How Common Is Cyberbullying Among Adults? Exploring Gender, Ethnic, and Age Differences in the Prevalence of Cyberbullying

Abstract: Previous research on cyberbullying has almost entirely focused on examining its prevalence among teens and young adults leaving it unclear how prevalent it is within the wider population. The present study used a New Zealand (NZ) national sample (N = 20,849) to examine gender, age, and ethnic differences in the experiences of cyberbullying victimization. On average, nearly 14.9 percent of respondents stated that they have ever been a target of cyberbullying before, with 2.2 percent respondents reporting such e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 22 publications
2
46
0
1
Order By: Relevance
“…For example, in France, we see that 14% of primary school students reported being victims of cyberbullying, while only 5% of secondary school students reported the same (Catherine and Michael, 2016). Other studies show that cyberbullying victimization decreases in prevalence as children grow older (Ševčíková and Šmahel, 2009;Wang et al, 2019). This variability may be explained by cultural differences and the level of access to technologies that students in different countries have.…”
Section: Introductionmentioning
confidence: 75%
“…For example, in France, we see that 14% of primary school students reported being victims of cyberbullying, while only 5% of secondary school students reported the same (Catherine and Michael, 2016). Other studies show that cyberbullying victimization decreases in prevalence as children grow older (Ševčíková and Šmahel, 2009;Wang et al, 2019). This variability may be explained by cultural differences and the level of access to technologies that students in different countries have.…”
Section: Introductionmentioning
confidence: 75%
“…In this way, it is confirmed that the socioeconomic aspects intervene and impact the CB due to the social nature of the phenomenon, thus being the most cited articles and, to a certain extent, most relevant to the scientific and academic community, those that collect contributions associated with the Social Sciences [124]. Among the most productive journals on this research topic, the second position of the International Journal of Environmental Research and Public Health (IJERPH) is remarkable, with 23 articles published in 2019, which represents 67.65% of the total on this topic, and, furthermore, all are classified in the thematic areas of Environmental Science and Medicine [125,126].…”
Section: Subject Areas and Journalsmentioning
confidence: 62%
“…In the study, cyberbullying got the most percentage compared to other negative impacts. cyberbullying is one of the causes of internet abuse from social media among teenagers [12] . Interactions on social media can be done without having to be face-to-face and can also interact with known and unknown people.…”
Section: The Origin Of Cyberbullyingmentioning
confidence: 99%